Analysis of the lateral push-off in the freestyle flip turn - Araujo L.* (2010)
The aim of this study was to examine the contact phase during the lateral push-off in the turn of front crawl swimming to determine which biomechanical variables (maximum normalized peak force, contact time, impulse, angle of knee flexion, and total turn time within 15 m) contribute to the performance of this turn technique. Thirty-four swimmers of state, national, and international competitive standard participated in the study. For data collection, the following equipment was used: an underwater force platform, a 30-Hz VHS video camera, and a MiniDv digital camera within an underwater box. Data are expressed as descriptive statistics. Inferential analyses were performed using Pearson's correlation and multiple linear regressions. All variables studied had a significant relationship with turn performance. We conclude that a turn executed with a knee flexion angle of between 100° and 120° provides optimum peak forces to generate impulses that allow the swimmer to lose less time in the turn without the need for an excessive force application and with less energy lost. © 2010 Taylor & Francis.